Digital Transformation, Digital Marketing Solutions for OCOP Subjects - Nguyen, Hoàng Giang; Tran, Lâm Duy; Vo, Đình Phụng (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2023)
In the context of globalization and the continuous development of technology, OCOP products play a vital role in promoting local economic and cultural values. OCOP products are typical products and services created or processed from local resources, bringing specific economic and cultural values. However, the reality shows that many OCOP subjects have not taken advantage of digital transformation and marketing to effectively bring products and services to consumers, making it difficult for the consumption of products and services in the highly competitive market. This article will discuss the current status of OCOP subjects, as well as synthesize scientific findings related to digital transformation and digital marketing. At the same time, the article will also give some recommendations and solutions for digital transformation and digital marketing for OCOP subjects, to help improve competitiveness and sustainable development.